Factors Affecting Consumers’ Intention to Use Jetts Fitness Centers in Bangkok. - เปี่ยมสุภัคพงศ์ ธีระศักดิ์; เปี่ยมสุภัคพงศ์ ธีระรัตน์; เปี่ยมสุภัคพงศ์ ฐิติพร; แก้วสถิตย์ ภัทราวุธ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1. examine the general characteristics of the respondents and the marketing mix factors; 2. compare the mean levels of consumers’ intention to use Jetts Fitness centers classified by personal factors; and 3. investigate the marketing mix factors influencing consumers’ intention to use Jetts Fitness centers. Data were collected from 385 users of Jetts Fitness centers in Bangkok using a questionnaire with convenience sampling. The data were analyzed using frequency, percentage, mean, standard deviation, t-test, one-way analysis of variance (ANOVA), factor analysis, and multiple regression analysis. The research findings revealed that: 1) the majority of respondents were male, aged between 26–35 years, single, company employees, holding a bachelor’s degree, and having an average monthly income of 20,001–30,000 baht. Overall, the marketing mix factors were rated at the highest level (x̄= 4.30, SD = 0.65); 2) differences in personal factors regarding income had a statistically significant effect on consumers’ intention to use Jetts Fitness centers at the 0.05 significance level; and 3) the marketing mix factor of process significantly influenced consumers’ intention to use Jetts Fitness centers at the 0.05 significance level. The estimated regression model could explain 46.6% of the variance in consumers’ intention.